การศึกษาสารสกัดคาร์โบฮัยเดรตจากเปลือกทุเรียนเพื่อใช้เป็นสารแขวนตะกอน - สุนันท์ พงษ์สามารถ (จุฬาลงกรณ์มหาวิทยาลัย, 1991)
Carbohydrate extracts from Durian (Durio zibethinus Linn.) rind were prepared in 2 fractions. Crude fraction (F I) was 60% alcohol precipitated from aqueous extract of fresh Durian rind (mesocarp). Purified fraction (F II) was purified by alcohol re-precipiatation of aqueous crude extract from acid-alcohol precipitation of aqueous extract of Durian rind. Preparation from these two methods gave 2.18% and 1.03% yield of F I and F II, respectively. Durian rind extracts were solid, amorphous powder, round and fiber shape were seen under scanning electron microscope. F I was light-brown in color, F II was creamy-white power. It had specific odor, sour and bitter tastes. F II from spray dried preparation was white fine powder, no bitter tastes, bubble-like shape was seen under scanning electron microscope. Powder of Drian rind extractes were swelled in water to give viscous liquid. Three percent preparation in water of F I was not a clear liquid, pale-brown in color, its viscosity was 130.6 cps and pH 5.8, where as F II was a colorless clear liquid, its viscosity was 207.6 cps and pH 2.8. Durian rind extracts were decomposed at 174-176 celcius degree. F I composes of carbohydrate 9.20% express as glucose, moisture 9.10% and ash 54.76%. F II composed of carbohydrate 9.49% express as glucose, moisture 12.00% and ash 41.45% Crude fiber was not found in Durian rind extracts. Elemenntal analysis of Durian rind extracts were found carbon (c) 19.33%, hydrogen (H) 2.72% in F I and found carbon 22.89%, and hydrogen 3.24% in F II. Nitrogen (N) was not existed in Durian rind extracts. Chemical analysis of Durian rind extracts were determined. Chemical property of carbohydrate was observed with Molisch s test and Anthrone test. Its showed reaction of glycuronate with Tollen s napthorescorcinol. Property of polysaccharide was observed with iodine solution giving purple-red color. No reducing sugar test was observed with Fehling s test. Only solution obtained from acid hydrolysis of F I and F II extracts showed reducing sugartest but lost their color formation with iodine. Durian rind extracts showed polyuronides property by forming gel precipitation with heavy metal solution and alcohol. Long chain polysacchrides of Durian rind extracts were hydrolysed by saliva amylase into short chain molecule that lose their color with iodine. However, digestion with amylase was not completed to give monosaccharids. Sugar components in polysaccharide of Durian rind extracts were determine by HPLC technique. F I composed of 4 monosaccharides indentacl yo standard rhamnose, arabinose, fructose and hlucose in 2:2:1:18 ratio. F II composed of 3 monosaccarides identical to standard rhamnose, arabinose and glucose in 1:1:3 ratio. Mineral analysis of Durian rind extracts showed high content of K 5.64% in F I and 2.21% in F II, ca 0.70% in F I and 1.02% in F II. Na and Mg were found in F I much more than F II. Other elements such as Al, Fe, Mn, Si Zn and Cu were low. Pb less than 0.08 ppm. Was found. Arsenic was not present in Durian rind extracts.Use of Durian rind extracts as suspending agent in suspension was studied. Durian extracts could be used satisfactorily in suspension of Kaolin Mixture with Pectin NF XIII. Good stability and redispersibility were observed after 60 days storage. Durian rind extracts could not be used in replacing CMC in Calamine Lotion. Gel formation was observed after 30 days storage and red redisperibility was fail after vigorpusly shake